Synthesis, characterization and biomedical applications of dye-doped silica nanoparticles - ISAAC ACQUAH, (International Journal of Pharma and Bio Sciences, 2019)
Dye-doped silica nanoparticles (NPs) are nanoscale material substrates that have received immense interest because of the favorable characteristics of silica. The advantageous attributes of silica include stability, ease of surface modification and bioconjugation, non-toxicity and hydrophilicity. However, in order to fully exploit the range of applicability of this amazing class of NPs, it is important to appreciate the methods of preparation of silica NPs, strategies to dope silica with dyes, characterization and some of the existing applications of dye-doped silica NPs. In this regard, this review looks at the various methods of synthesis of silica NPs as well as elucidating the underlying mechanism of particle formation. Physical and chemical techniques employed to incorporate dyes into silica NPs have also been presented. Some of the characterization tools utilized to explore the physicochemical properties of dye-doped silica NPs are introduced. In addition, the usage of dye-doped silica NPs for bioimaging, biosensing and gas sensing applications are also discussed. This work concludes with a look at some of the future prospects of dye-doped silica NPs.